Controllable one step copper coating on carbon nanofibers for flexible cholesterol biosensor substrates. Issue 2 (2nd December 2015) - Bajaj, Bharat; Joh, Han I.; Jo, Seong M.; Kaur, Gurpreet; Sharma, Anjali; Tomar, Monika; Gupta, Vinay; Lee, Sungho
Abstract : Electrospun carbon nanofibers (CNFs) decorated with copper oxide nanoparticles were successfully synthesized using a one step and modified hydroxyl ion assisted alcohol reduction method. Abstract : Electrospun carbon nanofibers (CNFs) decorated with copper oxide nanoparticles were successfully synthesized using a one step and modified hydroxyl ion assisted alcohol reduction method. The X-ray diffraction pattern reveals the presence of (−111), (111) and (−202) crystal planes of monoclinic copper oxide (CuO). The CuO coated CNF air annealed at 250 °C exhibited an electrical conductivity of 251 S m −1 . The CuO coated CNFs were employed as a novel flexible matrix for a cholesterol biosensor. The biosensor exhibited a high sensitivity of 75 μA mM −1 cm −2 over the linear range (0.12 mM to 12.93 mM) of cholesterol. This coating method offers easy and inexpensive processing with a flexible and robust supporting structure for biosensing applications.